Social and assistance characteristics of child and adolescent referrals to mental health services - Soares Gondim, Ana Paula; Parente Monteiro, Mirian; Onocko-Campos, Rosana Teresa; David Woods; Pessoa Maciel, Ana Paula; Duarte, Renata de Paula (O Mundo da Saúde, 2019)
The objective of the study was to compare the social, demographic and service characteristics of children and adolescents attended by mental health services in a Metropolitan Region of Northeast Brazil. This was a cross-sectional study with children and adolescents assisted by these services. The independent variables (service of the first appointment that referred the children and adolescents) and dependent variables (age, schooling, housing situation, family income and others) were examined. The users of these services came from the school (10.3%) and primary health care (30%) and had a mean age of 10 years. Most lived in their own home, with up to five residents and the family income was less than or equal to R$ 832.00. The majority received some type of government assistance 80.3%, and 77.3% of them received from the Bolsa Família Program. The bivariate analysis of primary care health referrals was significance for the ages of 1 to 12 years. While the bivariate analysis of school referrals identified a statistical significance for other levels of schooling and family income below R$ 832.00. The multiple logistic regression model showed a statistical significance for the family income variable below R$ 832.00. The important role of social and economic characteristics in the life and family of these children and adolescents defines the need to offer more effective actions to promote health and should integrate the context of education and health. Thus, it is possible to offer a contextualized extension of social and economic policies to these families in order to stimulate healthy environments.